ЗАЛЕЖНІСТЬ ВТРАТ ЕЛЕКТРИЧНОЇ ЕНЕРГІЇ ПРИ ЕНЕРГООБМІНІ КОНДЕНСАТОРІВ ВІД ЇХНІХ ПОЧАТКОВИХ НАПРУГ ТА СПІВВІДНОШЕННЯ ЄМНОСТЕЙ - Щерба, А.А.; Супруновська, Н.І. (Інститут електродинаміки НАН України, Київ, 2016)
The processes of electrical energy exchange between two connected capacitors of different capacity charged to different voltages are studied. The features of influence of the ratio of capacitor capacities, as well as their initial voltages on a loss of electric energy during its redistribution between the capacitors are determined. The conditions of decrease of such losses and increase of coefficient of energy transfer from one capacitor to another one are defined. References 10, figures 2, table 1.